Clinical Implications and Determinants of Left Atrial Mechanical Dysfunction in Patients With Stroke. Issue 6 (June 2016) - Kim, Darae; Shim, Chi Young; Hong, Geu-Ru; Kim, Mi-Hyun; Seo, Jiwon; Cho, In Jeong; Kim, Young Dae; Chang, Hyuk-Jae; Ha, Jong-Won; Heo, Ji Hoe; Chung, Namsik
Abstract : Background and Purpose—: The evaluation of sources of cardioembolism with transesophageal echocardiography (TEE) in patients with stroke is crucial but semi-invasive. We hypothesized that the size and mechanical function of the left atrium (LA) assessed by transthoracic echocardiography (TTE) could provide useful information on high risk of cardioembolism on TEE in patients with stroke. Furthermore, we sought to define the determinants of LA mechanical dysfunction in these patients. Methods—: A total of 248 patients with acute ischemic stroke (147 men; 64±13 years) who underwent 2-dimensional and speckle tracking TTE followed by TEE were analyzed. Results—: LA appendage emptying velocity, prevalence of LA or LA appendage thrombus, prevalence of aortic plaques, and incidence of embolic stroke showed significant differences among the 4 groups classified according to the median values of the LA volume index and global LA longitudinal strain (LALS). Patients at high risk of cardioembolism evidenced by TEE revealed significantly larger LA volume index and lower global LALS than those without. Global LALS (cutoff, 11.5%; area under the curve, 0.947; sensitivity, 100%; specificity, 91%; P <0.001) revealed a significantly better diagnostic power ( P =0.04) for LA or LA appendage thrombus than LA volume index (cutoff, 36.2 mL/m 2 ; area under the curve, 0.823; sensitivity, 88%; specificity, 75%; P =0.002). Age, left ventricular systolic function, LA volume index, and pulse wave velocity were independent determinants for global LALS. Conclusions—: LA mechanical dysfunction is closely associated with high risks of cardioembolism. Global LALS assessed by speckle tracking TTE well discriminates the presence of LA or LA appendage thrombus on TEE in patients with acute ischemic stroke. Abstract : Supplemental Digital Content is available in the text.